Rifaximin Improves Visceral Hyperalgesia via TRPV1 by Modulating Intestinal Flora in the Water Avoidance Stressed Rat - Chang-qing Yang; Xiao-shu Guo; Ji-Li; Zi-bai Wei; Li Zhao; Gan-ting Zhao; Shu-ting Sheng (Gastroenterology Research and Practice)
Background. Rifaximin is effective in relieving pain symptoms with IBS patients, although the mechanisms were not clear. The aims of the research were to investigate whether the visceral hyperalgesia was alleviated by rifaximin via TRPV1 channel in rats. Methods. Rats were subjected to water avoidance stress (WAS) and were pretreated with rifaximin by oral gavage. The visceromotor response to colorectal distension was measured. The changes of TRPV1 in peripheral and central neurons of rats were detected by immunofluorescence, western blot method, and RT-PCR. Bacterial 16S ribosomal DNA in ileal contents was assessed using the Illumina MiSeq platform. The effect of intestinal flora on TRPV1 channel was observed by fecal microbiota transplantation (FMT) methods. Results. Rifaximin could relieve the visceral hyperalgesia and reduce the TRPV1 expression of neurons and ileum mucosa in rats induced by WAS. The reduced relative abundance of intestinal flora induced by WAS could be partly prevented by rifaximin. The electromyographical activities and immunoreactivity of TRPV1 in rats could be changed after FMT. Conclusions. Rifaximin could improve visceral hyperalgesia via TRPV1 channels of peripheral and central neurons by modulating intestinal flora in rats.